EFEKTIVITAS PELAKSANAAN PROGRAM USAHA PENINGKATAN PENDAPATAN KELUARGA SEJAHTERA DI DESA MEDAN KRIO KECAMATAN SUNGGAL KABUPATEN DELI SERDANG - MARGARED DWI VERA HASIBUAN (Welfare StatE, 2013)
This thesis entitled "The Effectiveness of Program Implementation of Prosperous Family Increasing Revenue Attemption at Medan Krio Village, District of Sunggal,  Deli Serdang". The purpose of this research is to describe the extent to which the effectiveness of program implementation of prosperous family increasing revenue attemption at Medan Krio Village, District of Sunggal,  Deli Serdang. Conclusions obtained through data analysis cover: (1)Government in carrying the public policy and which lead to social policy namely social empowerment through UPPKS program, which goal is to empower ladies/woman in the field of economic as an effort to increase the poverty alleviation, also, in order to establish the self-reliance and  the family resilience as well as actualizing little, happy, and prosperous families. (2)The UPPKS Program which is carried out in Medan Krio Village  runs effectively, through the results of the calculation which is equal to 6.16% by using evaluative techniques. This can be determined by measuring the effectiveness of program understanding, target accuracy, time accuracy, target achievement, goal achievement, and tangible change from the UPPKS Program so that it can be seen that the conducted UPPKS program can be achieved well.     Key words : Effectiveness, Program UPPKS